PRINCIPLES IN ISLAMIC RELIGIOUS EDUCATION CURRICULUM (PAI) DEVELOPMENT - Muhammad Nur Irvanul Akbar; Muhammad Imam Khoirul Anam; Muhammad Muhajirin; Heny Kusmawati (Sean Institute, 2023)
The curriculum is one of the most important factors in the implementation of education, because the curriculum is the benchmark that will be conveyed by the teacher to his students. Therefore, the curriculum must also be adapted to the needs of students, so that the curriculum must go through a development phase, especially in the Islamic Religious Education (PAI) curriculum. From the development of the PAI curriculum, a foundation is needed so that the curriculum can be applied, namely with the principles of the PAI curriculum. This study aims to review the principles of Islamic Religious Education (PAI) curriculum development which are the main foundation in curriculum development.